ANALISA PERBANDINGAN PERFORMANSI SINGLE DAN DOUBLE TURBOCHARGER PADA CUMMINS ENGINE K50 SERIES - Hein Hein; Puji Saksono; Gunawan Gunawan (University of Merdeka Malang, 2016)
Application development engine in the heavy equipment is currently lead to the development of environmentally friendly technologies but with a better performance without changing the size or dimensions of the engine. Performance comparison analysis between Cummins engine applications which use single and double turbocharger to the performance, efficiency and fuel comsumtion required to provide a reference for users of heavy equipment unit (customer). This research was conducted at PT. Altrak Balikpapan branch in 1978 as a distributor of Cummins engines Indonesia. The research object is the Cummins engine type